Associations between electronic devices use and common mental traits: A gene–environment interaction model using the UK Biobank data. (7th December 2021) - Ye, Jing; Cheng, Shiqiang; Chu, Xiaomeng; Wen, Yan; Cheng, Bolun; Liu, Li; Liang, Chujun; Kafle, Om Prakash; Jia, Yumeng; Wu, Cuiyan; Wang, Sen; Wang, Xi; et al.
Abstract: Background: Electronic devices use has been reported to be associated with depression. However, limited effort has been provided to elucidate the associations between electronic devices use and mental traits in interaction with genetic factors. Methods: We first conducted an observational study consisting of 138 976–383 742 participants for TV watching, 29 636–38 599 participants for computer using and 118 61–330 985 participants for computer playing in the UK Biobank cohort. A linear regression model was used to evaluate the associations between common mental traits and electronic devices use. Subsequently, a genome‐wide gene–environment interaction study (GWEIS) was performed by PLINK2.0 to estimate the interaction effects of genes and electronic devices use on the risks of the four mental traits. Results: In the UK Biobank cohort, significant associations were observed between electronic devices use and mental traits (all P  < 1.0 × 10 −9 ), including depression score (B = 0.094 for TV watching), anxiety score (B = 0.051 for TV watching), cigarette smoking (B = 0.046 for computer using) and alcohol drinking (B = 0.010 for computer playing). GWEIS identified multiple mental traits associated loci, interacting with electronic devices use, such as DCDC2 (rs115986722, P  = 4.10 × 10 −10 ) for anxiety score and TV watching, PRKCE (rs56181965, P  = 9.64 × 10 −10 ) for smoking and computer using and FRMD4A (rs56227933, P  = 7.42 × 10 −11 ) for depression score and computer playing. Conclusions: Our findings suggested that electronic devices use was associated with common mental traits and provided new clues for understanding genetic architecture of mental traits. Abstract : Investigating the associations between electronic devices use and mental disorders from a genetic perspective